PELATIHAN PEMBUATAN DAN PEMANFAATAN PUPUK ORGANIK BERBAHAN DASAR SAMPAH/LIMBAH RUMAH TANGGA - Maria Y. M. A. Sumakud; Euis ., Pangemanan (EUGENIA, 2021)
This PKM activity is aimed at Catholic Women in Airmadidi, North Minahasa Regency. In the initial survey, the target community expects knowledge and skills about making organic fertilizers. Because it coincided with the pandemic, the implementation of PKM activities was carried out through the zoom application with the delivery of material by resource persons about the benefits of using organic fertilizers and the potential of existing resources around/around the environment that can be used as a source of organic fertilizer. After that, through a video, they demonstrated how to make organic fertilizer by utilizing existing resources. This training on making organic fertilizers needs to be followed up with mentoring activities during manufacture to further refine and maximize the results of the activities. In addition to household waste, various other biological sources can also be tried as a source of organic fertilizer. The community needs to get higher motivation so that they want to continue to make and produce and utilize organic fertilizers by utilizing the biological resources that exist around them